Identity of NU and Muhammadiyah groups; Gender Communication Studies - Hamidah, Lilik; Retpitasari, Ellyda (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
Every communication behaviour in society has a concept of mindset and ideology called behaviour as a structure in culture. This study examines the gender communication of community groups based on the NU and Muhammadiyah traditions. The research method used in this research is qualitative research with a critical ethnographic approach. The results show that the gender identity of the Tanggulangin Sidoarjo community comes from the teachings of religion and local Javanese culture. Religious sources are taken by studying holy books, and local cultural authorities are taken through four Javanese expressions: wanito, short for wani ditoto, Javanese terms macak, cook, manak, and konco wingking, swargo nunut neroko katut.